Penerapan Matching pada Graf untuk Pendistribusian Pupuk Bersubsidi dengan Metode Hungarian - Eva Wahyu Listyawati; Siti Amiroch; Novita Eka Chandra (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2020)
Increasing yields, demanding each farmer to improve the quality of agriculture, which in turn is expected to increase profits. The purpose of this paper is to determine the allocation of subsidized fertilizer distribution by the distributor of PT. Anak Gresik Raya Kencana and looking for the maximum number of subsidized fertilizer needs distributed in Lamongan district each year so that there is no scarcity and HET (Highest Retail Price) does not increase by applying the hungarian method. In this case, the problem is expressed as a bipartite graph, especially a complete weighted bipartite graph that applies the concept of matching, which is a perfect matching search with maximum weight using the Hungarian method. Matching is said to be perfect if it has fulfilled all the sets of vertices X and Y. Obtained the results of the allocation of subsidized fertilizer distribution by the distributor of PT. Anak Gresik Raya Kencana is Deket sub-district requiring 1220 tons of SP-36, Glagah sub-district requires 3208 tons of Urea, Karangbinangun sub-district requires 483 tons of Organic, mantup sub-district requires 2079 tons of ZA, middle district needs 2233 tons of NPK and fertilizer distribution problems subsidized in Lamongan district can be completed with the maximum amount of subsidized fertilizer needs distributed as many as 9223 tons every year